Chronic psychosocial stress does not affect the number of pyramidal neurons in tree shrew hippocampus - Vollmann-Honsdorf, Gesa K; Flügge, Gabriele; Fuchs, Eberhard (Neuroscience letters, 1997)
Exposure of the hippocampus for prolonged periods to an excess of glucocorticoids is thought to result in damage and finally loss of pyramidal neurons. By applying improved methods for quantifying cell numbers we investigated whether chronic psychosocial stress in tree shrews reduces the total number of hippocampal pyramidal neurons. For 28 days male tree shrews were exposed to subordination stress resulting in constantly elevated cortisol levels. The number of pyramidal neurons in the hippocampal fields CA1 and CA3 was estimated with the optical fractionator technique. In both hippocampal fields, neuron number in the stressed subjects was not significantly altered in comparison to unstressed controls. This constancy of neuron number represents an essential finding for identifying the effects of chronic stressful conditions on hippocampal structure.